ABOUT THE DICTATORSHIP OF THE PROLETARIAT - Anatoli Dmitrievich Shutov (Проблемы постсоветского пространства)
This paper investigates one of the most controversial historical issues - the theory and practice of revolutionary struggle, including the dictatorship of the proletariat. Much attention is focused on the issues of “dictatorship of the proletariat” and terms “government by the people” and “people’s power”.